2015
DOI: 10.1039/c5cp03617h
|View full text |Cite
|
Sign up to set email alerts
|

The properties of substituted 3D-aromatic neutral carboranes: the potential for σ-hole bonding

Abstract: The calculated properties of substituted carboranes such as dipole moment, polarisability, the magnitude of the σ-hole and the desolvation free energy are compared with these properties in comparable aromatic and cyclic aliphatic organic compounds. Dispersion and charge transfer energies are similar. However, the predicted strength of the halogen bonds with the same electron donor (based on the magnitude of the σ-hole) is larger for neutral C-vertex halogen-substituted carboranes than for their organic counter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 53 publications
2
23
1
Order By: Relevance
“…Recently, we studied the properties of halogenated carboranes using quantum mechanics (QM) methods. These calculations showed that halogenated carboranes had large and highly positive σ‐holes when an X atom was covalently attached to the C‐vertex of a neutral carborane molecule …”
Section: Figurementioning
confidence: 99%
“…Recently, we studied the properties of halogenated carboranes using quantum mechanics (QM) methods. These calculations showed that halogenated carboranes had large and highly positive σ‐holes when an X atom was covalently attached to the C‐vertex of a neutral carborane molecule …”
Section: Figurementioning
confidence: 99%
“…The strength of σ‐hole bonding can be inferred from the σ‐hole magnitude (V S,max ), which is defined as the most positive value of the ESP surface . The more positive the V S,max value, the stronger the X‐bond ,. The V S,max value depends on various characteristics of moieties appended to the X‐containing molecule, such as polarisability, electronegativity and electron‐withdrawing capability .…”
Section: Introductionmentioning
confidence: 99%
“…The more positive the V S,max value, the stronger the X‐bond ,. The V S,max value depends on various characteristics of moieties appended to the X‐containing molecule, such as polarisability, electronegativity and electron‐withdrawing capability . The properties of a σ‐hole (such as the V S,max value) can thus be modulated by substituting certain moieties on the molecule of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in YBs, as well as in other non-covalent interactions, the importance of the electrostatic interaction term is uppermost [426,437]. Several works have been carried out regarding the tunability of the mentioned σ -holes in different types of interactions, including halogen, chalcogen, and pnicogen [438,439,440,441]. In particular, the effect on the σ -hole upon substitution on aromatic rings has been previously studied [438,442,443,444].…”
Section: The Importance In Drug Design Of Similar To Hb Bondsmentioning
confidence: 99%